Gender Differences in Physics Achievement: Instructional Approach in Stem Learning Context to the Rescue (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Study focused on investigating the effectiveness of using an instructional approach in STEM leaning context to reducing or eradicating gender differences in physics achievements. A developed instructional module in STEM context for learning physics concepts was used for the study. Modules were validated by experts for face and content validity before usage in the study. Study was carried out in an afterschool environment. The developed instructional modules. Modules were subjected to use for learning the selected physics concepts in a single group design comprising of 48 male students and 41 female students in purposively selected secondary schools. Findings revealed that activities in STEM context had positive impacts on improving learners’ knowledge and arousing their curiosity to learning perceived physics concepts as against the usual conventional method. Moreover, study found out that learning physics concepts in the context of of STEM learning, developed the secondary school girls’ enthusiasm for the acquisition of skills in science, technology, engineering, and mathematics (STEM). Through the engaged hands-on STEM activities, the girls were able to explore, ask questions, show persistence and solved problem. The STEM instructional approach used in the study for learning physics concepts fuelled the students’ curiosity especially the females through creative thinking and problem solving so that through the positive feelings associated with the STEM learning, the school girls were more able to find learning physics more pleasurable and increasingly interesting. Thus, these positive experiences improved both male and female students’ achievement in physics learning. Study therefore recommended the use of STEM instructional approach in the learning of physics concepts to rescue from the common scenario of gender differences in physics achievement.